PWE-146 Biliary invasion in colorectal liver metastasis—does it matter?. (28th May 2012) - John, S K P; Rehman, S; Harrison, B; Robinson, S; Haugk, B; Manas, D; White, S
Abstract : Introduction: Vascular invasion of colorectal liver metastasis following liver resection has a detrimental effect on patient outcome. However there are few studies specifically looking at the significance of biliary invasion in colorectal liver metastasis (CRLM). The aim of this study was therefore to evaluate the presence of biliary invasion and patient outcomes in those having liver resection for CRLM. Methods: All patients having liver resection for colorectal liver metastasis during an 11-year period up to 2011 were identified from a prospectively maintained database. The unit follows standardised pathological reporting for CRLM where biliary and vascular invasion are assessed and documented. Missing information was specifically crosschecked with a separate histopathology database. Univariate and subsequent multivariate analysis were carried out for biliary and vascular invasion individually and in combination with other prognostic variables to assess their clinical significance. Survival was assessed using Kaplan–Meier plots and log rank tests for significance (p<0.05) using SPSS V.19. Results: 432 patients (67% male, mean age 64.5 years, range 29–86) underwent liver resection for CRLM during this time period. Primary tumours were either colonic (54%) or rectal (46%). Seventy patients (16.3%) had positive biliary invasion on tumour histopathology whereas 137 (32%) had vascular invasion. Overall 155 (36%) patients had both biliary and vascular invasion (BVI). Overall 5-year survival was 43% in this series. On univariate analysis 5-year survival in those patients with biliary invasion was 39.9% compared to 42.5% in those without biliary invasion (p=0.866). Results were similar in those patients with or without vascular invasion respectively (40.4% vs 43.2%, p=0.65). Also combined BVI failed to influence OS (39.2% vs 42.2%, p=0.856). Conclusion: In our series, bilary invasion of CRLM does not affect overall survival rates in patients having liver resection. Competing interests: None declared.